The Added Value of the “Co” in Co-Culture Systems in Research on Osteoarthritis Pathology and Treatment Development - Muenzebrock, Katrin Agnes; Kersten, Valerie; Alblas, Jacqueline; Garcia, Joao Pedro; Creemers, Laura B. (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is a highly prevalent disease and a major health burden. Its development and progression are influenced by factors such as age, obesity or joint overuse. As a whole organ disease OA affects not only cartilage, bone and synovium but also ligaments, fatty or nervous tissue surrounding the joint. These joint tissues interact with each other and understanding this interaction is important in developing novel treatments. To incorporate and study these interactions in OA research, several co-culture models have evolved. They combine two or more cell types or tissues and investigate the influence of amongst others inflammatory or degenerative stimuli seen in OA. This review focuses on co-cultures and the differential processes occurring in a given tissue or cell as a consequence of being combined with another joint cell type or tissue, and/or the extent to which a co-culture mimics the in vivo processes. Most co-culture models depart from synovial lining and cartilage culture, but also fat pad and bone have been included. Not all of the models appear to reflect the postulated in vivo OA pathophysiology, although some of the discrepancies may indicate current assumptions on this process are not entirely valid. Systematic analysis of the mutual influence the separate compartments in a given model exert on each other and validation against in vivo or ex vivo observation is still largely lacking and would increase their added value as in vitro OA models.